What We Talk About When We Talk About Binge Drinking: Towards an Integrated Conceptualization and Evaluation. (19th June 2020) - Maurage, Pierre; Lannoy, Séverine; Mange, Jessica; Grynberg, Delphine; Beaunieux, Hélène; Banovic, Ingrid; Gierski, Fabien; Naassila, Mickaël
Abstract: Rationale: Binge drinking (BD), characterized by recurring alternations between intense intoxication episodes and abstinence periods, is the most frequent alcohol consumption pattern in youth and is growing in prevalence among older adults. Many studies have underlined the specific harmful impact of this habit by showing impaired abilities in a wide range of cognitive functions among binge drinkers, as well as modifications of brain structure and function. Aims: Several controversies and inconsistencies currently hamper the harmonious development of the field and the recognition of BD as a specific alcohol consumption pattern. The main concern is the absence of consensual BD conceptualization, leading to variability in experimental group selection and alcohol consumption evaluation. The present paper aims at overcoming this key issue through a two-step approach. Methods and conclusions: First, a literature review allows proposing an integrated BD conceptualization, distinguishing it from other subclinical alcohol consumption patterns. Six specific characteristics of BD are identified, namely, (1) the presence of physiological symptoms related to BD episodes, (2) the presence of psychological symptoms related to BD episodes, (3) the ratio of BD episodes compared to all alcohol drinking occasions, (4) the frequency of BD episodes, (5) the consumption speed and (6) the alternation between BD episodes and soberness periods. Second, capitalizing on this conceptual clarification, we propose an evaluation protocol jointly measuring these six BD characteristics. Finally, several research perspectives are presented to refine the proposed conceptualization.